The Current Development and Outlook of China Certified Emission Reduction Trading Scheme - Lei ZHU; Mou WANG; Desheng HUANG; Yunqi LU (Chinese Journal of Urban and Environmental Studies)
China’s trading scheme for voluntary greenhouse gas (GHG) emission reductions, i.e. China Certified Emission Reduction (CCER), is an important policy tool to promote GHG emission reduction through market mechanisms and help achieve carbon peaking and carbon neutrality goals (the “dual carbon” goals). The CCER trading scheme was initiated in 2012, and after five years of practical exploration, it has provided an effective channel for the whole society to actively participate in carbon emission reductions. Since 2023, the relevant state departments have issued the Measures for the Administration of Voluntary Greenhouse Gas Emission Reduction Trading (Trial) and released the first batch of four project-specific methodologies and five verification institutions, marking the basic completion of the institutional framework of the CCER trading market. In January 2024, the CCER trading market was officially launched, and has been operated in a stable and orderly way, with its policy role of low-cost emission reduction through market mechanisms gradually coming into play. It should be also noted that, in the early stage of its start-up, the market still faces problems such as insufficient market supply, uncertain integration with international schemes, and relatively lagging behind in capacity building, which need to be gradually addressed in the development process. On that basis, this paper gives an outlook.